On-demand multiple route maintenance in AODV extensions (ORMAD) - Zahary, Ammar; Ayesh, Aladdin (IEEE, 2008)
This paper aims to improve routing fault tolerance in mobile ad hoc networks by optimizing multipath routing in traditional AODV routing protocol. It tries to prove the effect of varying waiting time of Route Reply (RREP) procedure and utilizing the concepts of threshold waiting time and efficient routes on the performance of multipath extensions to AODV. A novel approach called ORMAD (On-demand Route maintenance in Multipath AoDv) is conducted in this paper as a link-disjoint extension to our existing approach called TRAODV. ORMAD tries to optimize routing overhead of both Route Discovery Process (RDP) and Route Maintenance Process (RMP) of multipath extensions to AODV. When detecting a link failure in the primary route, ORMAD invokes a local repair procedure between the upstream and the downstream nodes of the broken link. Unlike ORMAD, TRAODV invokes a local repair procedure at the upstream node of the broken link to reach the destination node, which causes more routing overhead. In addition, ORMAD applies RMP only to the efficient routes, which leads to enhance route efficiency and consequently minimizes routing overhead. ORMAD is implemented using NS2 and evaluated against three multipath extensions to AODV protocol; TRAODV, MRAODV, and AOMDV. Results show that the performance is affected by varying the RREP waiting times of both phases RDP and RMP in different scenarios. ORMAD enhances routing packets overhead and average end-to-end delay compared to TRAODV and the other protocols, especially in high mobility scenarios.